2020
DOI: 10.1101/2020.07.16.207027
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reactivity-based screening for citrulline-containing natural products reveals a family of bacterial peptidyl arginine deiminases

Abstract: Ribosomally synthesized and post-translationally modified peptides (RiPPs) are a family of natural products defined by a genetically encoded precursor peptide that is tailored by associated biosynthetic enzymes to form the mature product. Lasso peptides are a class of RiPP defined by an isopeptide linkage between the N-terminal amine and an internal Asp/Glu residue with the C-terminus threaded through the macrocycle. This unique lariat topology, which provides considerable stability towards heat and proteases,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…3,17,24,25 Beyond the minimal BGC required for lasso peptide biosynthesis and commonly associated transporters and isopeptidases, genome mining of the ever-growing database of bacterial genome sequences 12 has revealed tailoring enzymes that subject lasso peptides to further post-translational modifications (PTMs). Modifications that have been confirmed experimentally include disulfide bonds, 26,27 C-terminal methylation, 19,28 acetylation, 29 citrullination, 30 phosphorylation, 31 glycosylation, 32 epimerization, 26,33 and β-hydroxylation. 6,34 All previously described lasso peptide PTMs occur in either the loop or tail regions of the lasso peptide, and these auxiliary enzymes recognize the linear precursor rather than the matured lasso as a substrate.…”
Section: ■ Introductionmentioning
confidence: 93%
“…3,17,24,25 Beyond the minimal BGC required for lasso peptide biosynthesis and commonly associated transporters and isopeptidases, genome mining of the ever-growing database of bacterial genome sequences 12 has revealed tailoring enzymes that subject lasso peptides to further post-translational modifications (PTMs). Modifications that have been confirmed experimentally include disulfide bonds, 26,27 C-terminal methylation, 19,28 acetylation, 29 citrullination, 30 phosphorylation, 31 glycosylation, 32 epimerization, 26,33 and β-hydroxylation. 6,34 All previously described lasso peptide PTMs occur in either the loop or tail regions of the lasso peptide, and these auxiliary enzymes recognize the linear precursor rather than the matured lasso as a substrate.…”
Section: ■ Introductionmentioning
confidence: 93%
“…This chemistry-based approach can be guided by genomic prioritization to only include strains capable of installing the targeted functional group, thus expediting natural product discovery. We have used reactivity-based screening to identify α/β-unsaturated carbonyl-containing natural products via 1,4-nucleophilic addition, reactive carbonyl-containing compounds via oxime ligation, and primary ureido-group-containing compounds via nucleophilic addition onto glyoxal-based probes. Other research groups have reported related approaches for elucidating the proteomic targets of natural products, chemoselective natural product enrichment, and methodology to covalently target di/trienes using a nitrosopyridine-based probe. To target the electron-rich polyene common to all GPMs (Supplemental Figure S1), we co-opted the well-known tetrazine ligation that was recently employed to detect isonitrile-containing natural products. , …”
Section: Introductionmentioning
confidence: 99%